2013
DOI: 10.1002/asi.22850
|View full text |Cite
|
Sign up to set email alerts
|

Citation content analysis (CCA): A framework for syntactic and semantic analysis of citation content

Abstract: This paper proposes a new framework for Citation Content Analysis (CCA), for syntactic and semantic analysis of citation content that can be used to better analyze the rich sociocultural context of research behavior. The framework could be considered the next generation of citation analysis. This paper briefly reviews the history and features of content analysis in traditional social sciences, and its previous application in Library and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 76 publications
(116 reference statements)
1
93
1
4
Order By: Relevance
“…It is proposed that this type of analysis be applied in the study of bibliographic citations, as part of citation content analysis, to detect the intention and disposition of the citing author to the cited work, and to give additional information to complement the calculation of the estimated impact of a publication to enhance its bibliometric analysis (Jbara and Radev, 2012). This analysis includes syntactic and semantic language relationships through speech and natural language processing and the explicit and implicit linguistic choices in the text to infer citation function and feelings of the author regarding the cited work (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that this type of analysis be applied in the study of bibliographic citations, as part of citation content analysis, to detect the intention and disposition of the citing author to the cited work, and to give additional information to complement the calculation of the estimated impact of a publication to enhance its bibliometric analysis (Jbara and Radev, 2012). This analysis includes syntactic and semantic language relationships through speech and natural language processing and the explicit and implicit linguistic choices in the text to infer citation function and feelings of the author regarding the cited work (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other limitation of this method is that a citation is interpreted as an author being influenced by the work of another, without specifying type of influence (Zhang et al, 2013) which can be misleading concerning the true impact of a citation (Young et al, 2008). To better understand the influence of a scientific work it is advisable to broaden the range of indicators to take into account factors like the author's disposition towards the reference, because, for instance, a criticized quoted work cannot have the same weight than other that is used as starting point of a research.…”
Section: Analyzing Argumentative Discourse Units In Online Interactionsmentioning
confidence: 99%
“…The method used for the data analysis of the third step was the citation content analysis [24], founded on the content analysis [25] and grounded theory [26]. This allowed a systematic, replicable compression of materials from the first and second step as codes and testing of hypotheses about both the quantity and quality of the scholarly influence of CLEF eHealth in 2012-2017.…”
Section: Methodsmentioning
confidence: 99%
“…Its results were supplemented by the known journal extensions of the CLEF eHealth overviews and previously enlisted papers that use the CLEF eHealth datasets [8]. WNs were technical reports written by participants describing their participation in the lab.Citation data for the resulting publication data was collected from Google Scholarone of the most comprehensive citation data sources in general and in particular for computer science, which is the main field of many CLEF eHealth scientists [9][10][11].The method used for the data analysis of the third step was the citation content analysis [24], founded on the content analysis [25] and grounded theory [26]. This allowed a systematic, replicable compression of materials from the first and second step as codes and testing of hypotheses about both the quantity and quality of the scholarly influence of CLEF eHealth in 2012-2017.…”
mentioning
confidence: 99%
“…Social science theories like homophily [23,24] and social influence [38] suggest that node attributes are highly correlated with network structure, i.e., the formation of one depends on and also influences the other. Examples include the strong association between user posts and following relationships in microblogging, and high correlation of paper topics and citations in academic networks [41]. In various applications, such as sentiment analysis [13] and trust prediction [33], it has been shown that jointly exploiting the two information sources can enhance the learning performance.…”
Section: Introductionmentioning
confidence: 99%